2023
DOI: 10.1109/access.2023.3340865
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Identification of Simultaneous Faults of Automotive Software Systems Under Noisy and Imbalanced Data Using Ensemble LSTM and Random Forest

Mohammad Abboush,
Christoph Knieke,
Andreas Rausch

Abstract: According to ISO 26262 standard, functional validation of the developed Automotive Software Systems (ASSs) is crucial to ensure the safety and reliability aspects. Hardware-in-the-loop (HIL) has been introduced as a reliable, safe and flexible test platform to enable the validation process in real-time. However, the traditional failure analysis process of HIL tests is time-consuming, extremely difficult and requires considerable effort. Therefore, an intelligent solution that can overcome the above challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…To put it in another way, two or more factors have contributed to creating a novel pattern in the signals as a result of the simultaneous FI. Detailed information regarding the setup of the simultaneous FI can be found at [45]. Figure 8c illustrates the effect of the simultaneous faults on the vehicle system behaviour, i.e., vehicle speed, between 170-330 s. The vehicle speed closely follows the desired behaviour up to 170 s, the time at which the faults are activated.…”
Section: Representative Time Series Datasetmentioning
confidence: 99%
“…To put it in another way, two or more factors have contributed to creating a novel pattern in the signals as a result of the simultaneous FI. Detailed information regarding the setup of the simultaneous FI can be found at [45]. Figure 8c illustrates the effect of the simultaneous faults on the vehicle system behaviour, i.e., vehicle speed, between 170-330 s. The vehicle speed closely follows the desired behaviour up to 170 s, the time at which the faults are activated.…”
Section: Representative Time Series Datasetmentioning
confidence: 99%
“…The motivation for exploring the evolution of vehicles with advanced driver-assistance systems (ADAS), autonomous driving capabilities, and Internet of Things (IoT) integrations lies in the increasing complexity of their operating systems [5]. Fault injection tests the reliability of these interconnected systems to ensure that a fault in one component does not lead to a comprehensive system breakdown [6].…”
Section: Introductionmentioning
confidence: 99%
“…Luca et al (2023) have presented a methodology for fault identification of dissolved oxygen sensors in wastewater treatment plants using the Fisher discriminant analysis to identify six sensor fault types, bias, drift, gain, precision degradation, fixed value, and complete failure. In automotive software systems, Abboush et al (2023) have reported a methodology to identify combined sensor faults using ensemble LSTM and random forest networks. In the field of mechatronic systems, Sergiyenko et al (2022) have introduced an approach for sensor fault identification via linear and nonlinear dynamic models using sliding mode observers.…”
Section: Introductionmentioning
confidence: 99%